Implementasi Program Kerja Bappeda Provinsi Jawa Barat Perspektif Peraturan Perundang-undangan dan Fiqih Siyasah - Nur Anisa Al Maulida; Siti Ngainnur Rohmah; Munawir Sajali (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Bappeda of West Java Province was formed to carry out the regional development planning mechanism in the future and is required to increasingly prioritize development planning that is transparent, accountable, and participatory. The aim of this research is to find out the implementation of work programs of Bappeda of West Java Province according to Law No. 25 of 2004 in the perspective of Fiqh Siyasah. The author uses a type of qualitative research with a normative juridical approach. The results of the research show that the Implementation of the Bappeda Work Program in West Java Province according to Law no. 25 of 2004 is in accordance with the implementation of accountability for the main tasks in development planning. Bappeda of West Java Province in implementing its work program is in accordance with the 4 foundations of Siyasah Fiqh, namely: Tauhid, Rububiyah, Khalifah, and Tazkiyah. This is in accordance with the concept of the development of Imam Al-Mawardi.Keywords: Implementation; Work program; Bappeda West Java Province; Law Number 25 of 2004; Fiqh Siyasa AbstrakBappeda Provinsi Jawa Barat dibentuk untuk menjalankan mekanisme perencanaan pembangunan daerah ke depan dan dituntut untuk semakin mengedepankan perencanaan pembangunan yang transparan, akuntable, dan partisipatif. Tujuan dari penelitian ini adalah untuk mengetahui implementasi program kerja Bappeda Provinsi Jawa Barat menurut Undang-undang Nomor 25 Tahun 2004 dalam perspektif Fiqih Siyasah. Penulis menggunakan jenis penelitian kualitatif dengan pendekatan yuridis normatif. Hasil penelitian menunjukkan Implementasi Program Kerja Bappeda Provinsi Jawa Barat menurut UU No. 25 Tahun 2004 sudah sesuai dengan implementasi pertanggungjawaban terhadap tugas pokok dalam perencanaan pembangunan. Bappeda Provinsi Jawa Barat dalam implementasi program kerjanya sudah sesuai dengan 4 landasan Fiqih Siyasah yaitu: Tauhid, Rububiyah, Khalifah, dan Tazkiyah. Hal tersebut sesuai dengan konsep pembangunan Imam Al-Mawardi.Kata Kunci: Implementasi; Program Kerja; Bappeda Provinsi Jawa Barat; Undang-Undang Nomor 25 Tahun 2004; Fiqih Siyasah